Nation-building and Turkish modernization Islam, Islamism, and nationalism in Turkey - Dönmez, Rasim Özgür; Yaman, Ali 1968 (Lexington Books, 2019)
This book analyzes the nation building process in Turkey from a socio-historical perspective. Authors compare the nation-building process in the Republic period with the pro-Islamists of the JDP period